Dynamic Analysis of Planar Linkage Mechanism Considering the Clearance of Kinematic Pair - Guoguang Jin; Xurui Hou; Zhan Wei; Zhimin Wang; Yanyan Song (Jixie chuandong)
In order to accurately analyze the influence of the kinematic pair clearance on the mechanism dynamic characteristics， a nonlinear stiffness coefficient is introduced based on the Gonthier contact force model， and an improved Gonthier model is obtained， which can more accurately describe the elastic force in the kinematic pair. The system dynamic equation of planar four-bar linkage with two-state clearance is established using Newton Euler equation， and the correctness of the clearance model is verified by Adams. The influence of different clearance， rotation speed and friction coefficient on the acceleration of the rocker is analyzed， and the contact and free states of the inner shaft of the kinematic pair are studied. The results show that the shaft has three states of collision， contact and freedom under certain conditions. After the system becomes stable， the shaft is always in contact with the kinematic pair， which indicates that the motion of the shaft in the kinematic pair is not random collision. The driving force of the mechanism is mainly transmitted by the contact force generated by the deformation of the contact point， rather than the collision force between the shaft and the bearing. The results can predict the position of the clearance， and have important theoretical value for restraining the vibration and wear of the mechanism caused by the clearance.